Targeting the profits of illicit drug trafficking through proceeds of crime action - Martin O&#039
This study sought to identify the disruptive effect of proceeds of crime action on criminal activity, and to identify factors associated with successful proceeds of crime action. Executive summary Illicit drug trafficking is a source of funds for further trafficking and for supporting the lifestyles of criminals. Drug trafficking has been closely linked with organised crime and with social harms. This project had two main aims: • To identify the disruptive effect of proceeds of crime action on criminal activity. The project attempted to measure the disruptive effect by developing an economic model that estimated the multiplier impact of the reinvestment of the profits of drug trafficking. • The project also attempted to identify factors associated with successful proceeds of crime action. There are two main audiences for the findings of this study. Senior police, police intelligence, policymakers and researchers will be interested primarily in measuring the disruptive effect of proceeds of crime action. Police responsible for managing proceeds of crime investigations and senior investigators will be interested in the practical applications of findings relating to success factors in financial investigations. The results of the project should improve agencies’ ability to target trafficking and increase the seizure of proceeds of crime. The proposed index of the disruptive effect of proceeds of crime action—the Proceeds of Crime Drug Disruption Index (POCDDI)—will also allow agencies to provide both the Government and the community with a more accurate assessment of the value of their proceeds of crime initiatives